2009
DOI: 10.1002/bsl.898
|View full text |Cite
|
Sign up to set email alerts
|

Comprehending Canadian police cautions: are the rights to silence and legal counsel understandable?

Abstract: Comprehension of a Canadian police right to silence caution and a right to legal counsel caution was examined. Each caution was first presented verbally in its entirety, followed by its sentence-by-sentence presentation in written format. Participants (N = 56) were asked to indicate, after each presentation, their understanding of the caution. When delivered in verbal format, 4 and 7% of participants fully understood the right to silence and legal counsel cautions, respectively. However, 48 and 32% of particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 18 publications
3
27
1
Order By: Relevance
“…It is imperative that interviewees understand the legal rights contained in those cautions so that their rights are protected and the police are able to ensure the admissibility of statements (Marin 2004;Whittemore and Ogloff 1994). Unfortunately, experimental studies in various countries, such as Canada, the United States, and the United Kingdom, have demonstrated that it is rare for people to understand fully the rights contained in police cautions (e.g., Cooke and Philip 1998;Eastwood and Snook 2009;Fenner, Gudjonsson, and Clare 2002;Grisso 1981). Such studies have typically presented the cautions in an ideal manner under highly controlled conditions.…”
Section: Introductionmentioning
confidence: 97%
“…It is imperative that interviewees understand the legal rights contained in those cautions so that their rights are protected and the police are able to ensure the admissibility of statements (Marin 2004;Whittemore and Ogloff 1994). Unfortunately, experimental studies in various countries, such as Canada, the United States, and the United Kingdom, have demonstrated that it is rare for people to understand fully the rights contained in police cautions (e.g., Cooke and Philip 1998;Eastwood and Snook 2009;Fenner, Gudjonsson, and Clare 2002;Grisso 1981). Such studies have typically presented the cautions in an ideal manner under highly controlled conditions.…”
Section: Introductionmentioning
confidence: 97%
“…In a related investigation, Eastwood and Snook (2010) examined Canadian undergraduate students' understanding of the right to silence caution, and the right to legal representation caution. They found that when the cautions were presented verbally in full, only 4% of participants fully understood the right to silence caution, while only 7% fully understood the right to legal representation caution.…”
Section: Introductionmentioning
confidence: 99%
“…see Eastwood & Snook, 2010). Once the suspect is under arrest, however, the warning typically takes this form: 'You are under arrest for the charge of ___.…”
Section: Safeguards Designed To Protect the Rights Of Defendants And mentioning
confidence: 97%
“…What is less clear is if suspects exercise these rights. Eastwood and Snook (2010) have demonstrated that University students in Newfoundland (half of whom were enrolled in a police recruit program) understood their right to remain silent and the right to legal counsel but had difficulty understanding that they had little to gain of 'hope from any promise or favor' or 'fear from any threat'.…”
Section: Safeguards Designed To Protect the Rights Of Defendants And mentioning
confidence: 98%
See 1 more Smart Citation